Soft errors in 10-nm-scale magnetic tunnel junctions exposed to high-energy heavy-ion radiation - Kobayashi, Daisuke; Hirose, Kazuyuki; Makino, Takahiro; Onoda, Shinobu; Ohshima, Takeshi; Ikeda, Shoji; Sato, Hideo; Enobio, Eli Christopher Inocencio; Endoh, Tetsuo; Ohno, Hideo (Japanese Journal of Applied Physics, 2017)
The influences of various types of high-energy heavy-ion radiation on 10-nm-scale CoFeB-MgO magnetic tunnel junctions with a perpendicular easy axis have been investigated. In addition to possible latent damage, which has already been pointed out in previous studies, high-energy heavy-ion bombardments demonstrated that the magnetic tunnel junctions may exhibit clear flips between their high- and low-resistance states designed for a digital bit 1 or 0. It was also demonstrated that flipped magnetic tunnel junctions still may provide proper memory functions such as read, write, and hold capabilities. These two findings proved that high-energy heavy ions can produce recoverable bit flips in magnetic tunnel junctions, i.e., soft errors. Data analyses suggested that the resistance flips stem from magnetization reversals of the ferromagnetic layers and that each of them is caused by a single strike of heavy ions. It was concurrently found that an ion strike does not always result in a flip, suggesting a stochastic process behind the flip. Experimental data also showed that the flip phenomenon is dependent on the device and heavy-ion characteristics. Among them, the diameter of the device and the linear energy transfer of the heavy ions were revealed as the key parameters. From their dependences, the physical mechanism behind the flip was discussed. It is likely that a 10-nm-scale ferromagnetic disk loses its magnetization due to a local temperature increase induced by a single strike of heavy ions; this demagnetization is followed by a cooling period associated with a possible stochastic recovery process. On the basis of this hypothesis, a simple analytical model was developed, and it was found that the model accounts for the results reasonably well. This model also predicted that magnetic tunnel junctions provide sufficiently high soft-error reliability for use in space, highlighting their advantage over their counterpart conventional semiconductor memories.